2006
DOI: 10.1038/sj.emboj.7601197
|View full text |Cite
|
Sign up to set email alerts
|

An 8 nt RNA triggers a rate-limiting shift of RNA polymerase II complexes into elongation

Abstract: To better understand the critical conversions that RNA polymerase II complexes undergo during promoter escape, we determined in vitro the precise positions of the ratelimiting step and the last step requiring negative superhelicity or TFIIE and TFIIH. We found that both steps occur after synthesis of an 8 nt RNA during the stage encompassing translocation of the polymerase active site to the ninth register. When added to reactions just before this step, TFIIE and TFIIH overcame the requirement for negative sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…The promoter DNA influences the level of transcription and the position at which RNA synthesis begins through sequences in the regulatory and core promoter elements (1,2). In addition, the conformation of promoter DNA can regulate the level of transcription, both in the presence and absence of histones (3)(4)(5)(6)(7). The general transcription factors, including TFIIA, TFIIB, TFIID, TFIIE, TFIIF, and TFIIH, are required for pol II to transcribe in a specific fashion in most, if not all, genes (8).…”
Section: From the Department Of Chemistry And Biochemistry Universitmentioning
confidence: 99%
See 4 more Smart Citations
“…The promoter DNA influences the level of transcription and the position at which RNA synthesis begins through sequences in the regulatory and core promoter elements (1,2). In addition, the conformation of promoter DNA can regulate the level of transcription, both in the presence and absence of histones (3)(4)(5)(6)(7). The general transcription factors, including TFIIA, TFIIB, TFIID, TFIIE, TFIIF, and TFIIH, are required for pol II to transcribe in a specific fashion in most, if not all, genes (8).…”
Section: From the Department Of Chemistry And Biochemistry Universitmentioning
confidence: 99%
“…Regulated genespecific transcription in cells requires a plethora of additional factors, including activators, repressors, co-regulators, and chromatin-modifying factors (2,6,8,9). In addition to the promoter and protein factors, biochemical studies have shown that the RNA transcript is not simply the product of the reaction, but it also stabilizes elongation complexes through the RNA: DNA hybrid and influences transformations that occur during early transcription (3,10,11). Although the core factors required for pol II to synthesize a transcript in vitro are understood, structural and biochemical studies are still uncovering new information about the mechanism by which this process occurs and is regulated.…”
Section: From the Department Of Chemistry And Biochemistry Universitmentioning
confidence: 99%
See 3 more Smart Citations